Enhancing Teachers’ Digital Pedagogy through ICT-Based Training at MIN 1 Padangsidimpuan - Khoirani Febry Dalimunthe; Indah Amaliyah Siregar; Anita Adinda (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The integration of information and communication technology (ICT) is essential for supporting student-centered learning and developing 21st-century skills. However, many primary school teachers still experience difficulties in implementing ICT meaningfully due to limited digital pedagogical competence and a lack of contextualized professional development, particularly in primary and Islamic school contexts. This study aims to explore the implementation and outcomes of an ICT-based teacher training programs conducted through a field study approach, focusing on its influence on teachers’ digital pedagogical competence and instructional practices. A qualitative descriptive field study design was employed. Participants were primary school teachers from an Islamic public school in Indonesia who took part in a six-session ICT training programs. Data were collected through observations, documentation of teachers’ digital products, and reflective field notes, and analyzed using thematic analysis. The findings reveal improvements in teachers’ pedagogical understanding of ICT, technical skills, and readiness for classroom implementation. Teachers produced various ICT-based learning media aligned with instructional objectives, including interactive quizzes, game-based activities, visual materials, animated videos, and digital classrooms. High levels of engagement and collaboration were observed despite infrastructural challenges. Field-based, practice-oriented ICT training effectively bridges technological skills and pedagogical application, supporting sustainable digital pedagogy in primary education.